2015
DOI: 10.1177/1362361315575164
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth delivery of cognitive-behavioral intervention to youth with autism spectrum disorder and anxiety: A pilot study

Abstract: Youth with autism spectrum disorders frequently experience significant symptoms of anxiety. Empirically supported psychosocial interventions exist, yet access is limited, especially for families in rural areas. Telehealth (i.e. videoconferencing) has potential to reduce barriers to access to care; however, little is known about the feasibility or efficacy of directly intervening with youth with autism spectrum disorders through this modality. This study details the pilot testing of a telehealth version of an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 44 publications
1
109
0
3
Order By: Relevance
“…One promising intervention that reduces the transportation and waiting burden on parents, especially in rural areas, is Facing your Fears. This "telehealth" program delivers cognitive behavior therapy for anxiety disorders to small groups of youth with ASD and their parents, through clinic-to-home videoconferencing (Hepburn et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One promising intervention that reduces the transportation and waiting burden on parents, especially in rural areas, is Facing your Fears. This "telehealth" program delivers cognitive behavior therapy for anxiety disorders to small groups of youth with ASD and their parents, through clinic-to-home videoconferencing (Hepburn et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…), with positive outcomes reported for communication and other skills, including behaviour and imitation, as well as to support older children with autism and co‐occurring anxiety (Hepburn et al . ) and to provide functional behavioural assessment and functional communication training for children with behaviour support needs (Lindgren et al . , Suess et al .…”
Section: Introductionmentioning
confidence: 99%
“…Telehealth has been found to be a viable method of service provision for families of children with autism who are unable to access local services, particularly in the preschool population. It has been used to provide parent training in early intervention (e.g., Ingersoll and Berger 2015, Meadan et al 2016, Wainer and Ingersoll 2015, Simacek et al 2017, with positive outcomes reported for communication and other skills, including behaviour and imitation, as well as to support older children with autism and co-occurring anxiety (Hepburn et al 2015) and to provide functional behavioural assessment and functional communication training for children with behaviour support needs (Lindgren et al 2016, Suess et al 2014) via parent training. Diagnostic assessments for autism have been completed via telehealth with adults (Schutte et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although telehealth approaches demonstrated feasibility to delivery psychosocial interventions in access-limited environment (Hepburn et al 2016), robust evaluation of population-based effectiveness was lacking and the usability of such new technology was somewhat problematic during implementation. In the absence of effective countermeasures to eliminate practical barriers, increasing universal access to psychosocial services in patients with brain function impairment remains a challenge In this study, use of psychosocial interventions increased in association with receiving intensive care or having comorbid mental illnesses.…”
Section: Discussionmentioning
confidence: 99%